Diglosia dalam Masyarakat Mentawai: Perspektif Sosiolinguistik - Gustiana, Gustiana; Mardi, Melia; Lestari, Frida Nur; Yasmanelly, Yasmanelly; Putri, Desmimi Eka; Aziz, Elfiondri (Universitas Islam Sumatera Utara, 2025)
This study aims to investigate (1) the types of languages used concurrently by speakers in Mentawai, and (2) the social, cultural, and educational factors influencing language choice across different contexts. A qualitative descriptive research method was employed to explore and present the data in narrative form. This approach is particularly suitable for uncovering linguistic practices and providing rich, in-depth descriptions of language use in a sociolinguistic setting. The study focuses on the phenomenon of diglossia in the Mentawai community from a sociolinguistic perspective. Given the complexity and contextual nature of social data, a qualitative approach allows for more accurate verification and interpretation of language practices, which might otherwise be obscured in purely quantitative research. The findings highlight that language choice in Mentawai is deeply influenced by social hierarchy, education, and cultural interactions, revealing a layered linguistic landscape shaped by both tradition and modernization.